The Effect of Discipline, Motivation, Work Environment on Employee Performance and Their Impact on Job Satisfaction Employees at Bank Muamalat Tulungagung Branch Office: Pengaruh Disiplin, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Serta Dampaknya Terhadap Kepuasan Kerja Karyawan Bank Muamalat Kcp Tulungagung - Anggi Putri Puryanti; Ahmad Supriyadi; Elok Fitriani Rafikasari (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
Job satisfaction, in addition to performance, is a component that determines the magnitude of organizational success. Job satisfaction influences performance because it is very important for the development of the company in order to increase employee productivity and performance, with several supporting factors including motivation, discipline and work environment. This study aims to determine the effect of work discipline on employee satisfaction, motivation on employee satisfaction, work environment on employee satisfaction, work discipline on employee performance, motivation on employee performance, work environment on employee performance and discipline, motivation and work environment on employee performance and the impact on employee satisfaction of Bank Muamalat Tulungagung Branch Office. This type of study is explanatory research, and the study method is quantitative. The population in this study amounted to 30 employees. The number of samples is 30 employees using the saturated sample technique (Path). This study uses descriptive quantitative analysis and statistical analysis to determine the direct and indirect relationship between work discipline, work motivation, work environment, employee performance, and job satisfaction variables. The results obtained both partially and simultaneously show that work discipline, work motivation and work environment variables have a positive and significant impact on employee performance through job satisfaction variables with a total effect of 72.9%. In comparison, the remaining 27.7% is influenced by other factors.